It Is Human Stupidity, Not Artificial Intelligence, That Threatens Our Future: I helped create the fear of Al. But those were novels, people. - Card, Orson Scott (Commentary, 2026)
The article argues that public fear of artificial intelligence (AI) is overstated, while weak education, poor judgment, and human misuse of technology pose far greater dangers to society. Topics include unreliable AI detection in education, the limits of machine-generated language and creativity, and the influence of science fiction on fears about intelligent machines.